SUOP AS THE TOOL OF LABOR SAFETY AND HEALTHOF WORKERS AT PRODUCTIONS - Беликов, Анатолий; Папирнык, Руслан; Taирова Тамара (SWorldJournal, 2020)
Abstract. In the article the author formulated the modern approach to the research of the system of labor protection as the pidsystem of the SOUP. The mathematical model of the labor protection system has been developed, the effectiveness of its function